Studi Literatur Peran Lembaga Keuangan Mikro Syariah Dalam Meningkatkan Kesejahteraan - Muhammad Arfan Harahap; Andri Soemitra (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to investigate the contribution of Islamic microfinance institutions in an effort to promote public welfare based on a selected literature review. The findings of this study unravel the gaps in the Islamic microfinance literature regarding the existence of Islamic microfinance institutions. The research design was carried out by collecting selected literature from the Scopus database and conducting a literature study on the research data. There are 25 articles with research results that strengthen the existence of Islamic financial institutions that contribute to efforts to promote prosperity. This is a new fact that LKMS can be used as a solution to poverty alleviation with its various unique characteristics. This study also found that the State of Malaysia was in first place in the publication of articles related to LKMS and was followed by the State of Indonesia. This study recommends that future research analyzes the comparative contribution between Islamic banks and Islamic microfinance institutions. Keywords: Islamic Microfinance Institutions, Literature, Welfare